2010
DOI: 10.1002/asia.200900690
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Gold(III) Complexes of Asymmetrically Aryl‐Substituted 1,2‐Dithiolene Ligands Featuring Potential‐Controlled Spectroscopic Properties

Abstract: The tetrabutylammonium (TBA(+)) salts of square-planar monoanionic gold complexes of the unsymmetrically substituted Ar,H-edt(2-) 1,2-dithiolene ligands (Ar,H-edt(2-)=arylethylene-1,2-dithiolato; Ar=phenyl (1(-)), 2-naphthyl (2(-)), and 1-pyrenyl (3(-))) were synthesized and characterized by spectroscopic and electrochemical methods and the corresponding neutral species (1, 2, and 3, respectively) were obtained in CH(2)Cl(2) solution at room temperature by diiodine oxidation. The single-crystal X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 55 publications
8
33
0
Order By: Relevance
“…Notwithstanding numerous attempts, no crystals suitable for X‐ray diffraction analysis were obtained for this compound. The spectroscopic and electrochemical features of (TBA + )( 1 − ) have been discussed previously and compared to those of (TBA + )( 2 − ) and (TBA + )( 3 − ) 21. The electrochemical behavior of the title complex reflects what is expected for this class of compounds.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Notwithstanding numerous attempts, no crystals suitable for X‐ray diffraction analysis were obtained for this compound. The spectroscopic and electrochemical features of (TBA + )( 1 − ) have been discussed previously and compared to those of (TBA + )( 2 − ) and (TBA + )( 3 − ) 21. The electrochemical behavior of the title complex reflects what is expected for this class of compounds.…”
Section: Resultsmentioning
confidence: 77%
“…The complex (TBA + )( 1 − ) was synthesized following the well‐established route of treating the corresponding vinylene dithiocarbonate (4‐pyren‐1‐yl‐[1,3]dithiol‐2‐one) with potassium tetrachloroaurate in the presence of tetrabutylammonium iodide 21. Notwithstanding numerous attempts, no crystals suitable for X‐ray diffraction analysis were obtained for this compound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility of tuning both the electrochemical and photophysical properties of these chromophores by systematically varying both the central metal ion 28 and the S^S and N^N ligand 29 was distinctly proved. In this context, some of the authors recently reported on a series of new Pt II diimine-dithiolate complexes featuring differently functionalized 1,2-dithiolato ligands belonging to the classes of R-edt 2− (monosubstituted ethylene-1,2-dithiolates; R = phenyl, 2-naphtyl, 1-pyrenyl) 30,31 and R-dmet 2− (N-substituted…”
Section: Introductionmentioning
confidence: 99%